Market entry, asset returns, and irrational exuberance: asset management anomalies in dry cargo shipping - Bulut, Emrah; Duru, Okan; Yoshida, Shigeru (INDERSCIENCE ENTERPRISES LTD, 2013)
The aim of this paper is to investigate shipping assets and market entry decisions from the point of business cycles in the dry cargo shipping. One of the critical problems of the shipping business is based on the market entry-exit decisions and the investment timing for asset allocation. There are many indicators which define the investment climate in the shipping business and the optimised market entry may extremely contribute the cumulative financial results of a shipping asset. A number of indicators are investigated under the business cycle perspective and the fluctuations of the return on equity (here after ROE) is figured out in the long-run framework. The fluctuations of asset prices and ROE indicate that the ship investor tends to place the investment at the time of peaks of asset prices (new building or second hand) which extremely causes the loss of ROE rates in long-run. The statistical significance is tested and the market entry decision is investigated according to the maximum ROE constraint.
Keywords: asset management; irrational exuberance; market entry-exit; dry bulk shipping; MODEL; Business & Economics; Transportation